Correlation analysis of expression of CC and CXC chemokines in children with autism spectrum disorder. Issue 24 (18th June 2021) - Peng, Guangyang; Peng, Xiaofei; Tong, Tingting; Zhang, Xiuyun; Xu, Min; Peng, Xiaofang
Abstract : Abstract: To investigate the relationship between the expression of CC and CXC chemokines and autism spectrum disorder (ASD). A total of 62 children with ASD (ASD group) and 60 gender- and age-matched normal children (control group) admitted to our hospital from January 2019 to January 2020 were included in the study. Monocyte chemoattractant protein-1 (MCP-1), macrophage inflammatory protein-1α (MIP-1α), macrophage inflammatory protein-1β (MIP-1β), regulated upon activation, normal T-cell expressed and secreted (RANTES), interleukin-8 (IL-8), monokine induced by interferon (IFN)-γ (MIG), and purified human interferon-γ-induced protein-10 (IP-10) were detected in the ASD group. The correlation between the above indexes and the severity of the ASD group was analyzed. Significantly increased MCP-1 levels ( P  < .01) along with the markedly decreased MIP-1α and MIP-1β levels ( P  < .01) were detected in the venous blood of the ASD group compared with the control group. In addition, they exhibited no significant difference (yet a downward trend) in the level of RANTES ( P  > .05). Children in the ASD group showed significantly decreased IP-10 levels ( P  < .01); however, they had no noticeable change (yet a decreasing trend) in the levels of IL-8 and MIG ( P  > .05). MCP-1 level was positively related to the Module 1 scores of Autism Diagnostic Observation Schedule-second edition (ADOS-2), whereas the levels of Childhood Autism Rating Scale MIP-1α, MIP-1β, IL-8, IP-10, and MIG were negatively correlated with the ADOS-2 Module 1 scores ( P  < .01). However, no significant correlation was found between RANTES and the ADOS-2 Module 1 scores ( P  > .05). The levels of CC chemokines (MCP-1, MIP-1α, MIP-1β, and RANTES) and CXC chemokines (IL-8, IP-10, and MIG) are positively correlated with the pathogenesis of ASD. Inflammation is an important contributing factor to ASD.